Study the Effect of Diameter and Depth of Parabolic Dish Collector on the Concentration Ratio and Temperature Amount of Solar Tower Receiver (Journal of University of Babylon for Engineering Sciences, 2019)
This work introduces three models of parabolic dish collectors with different dimension to study the effect of change diameter and depth of the dish on the position of focus point and concentration ratio and the temperature of outlet hot water or steam by using different receivers. The present work deals with a new system consists of dish and receiver to produce hot water and steam from solar energy. The parabolic dish solar collector fabricated from iron with different dimension the first model with diameter (82 cm) and depth (6 cm), this gives focus length (70cm) and Concentration ratio (25.6). The second model with a diameter (100cm) and depth (3 cm), this give focus length (208cm) and concentration ratio (15). The third model with a diameter  (150cm) and depth (12cm), This give focus length (100cm) and concentration ratio (399) and the front side covered by nickel sheet metal to focus the solar radiation upon the receiver for all models  . Three different shapes of receiver tanks used with the third model ; namely case one which used rectangular receiver tank (100×50×5) cm3 filled with 25 liter of water. Case two used helical copper coil (12.5 mm× 3 m) inside aluminum cylindrical vessel (0.2 m ×0.6 m). Case three used radiator heat exchanger receiver tank (37×47×4) cm3 filled with 3 liter of water. Use low cost and available materials to manufacture the experimental part. The dish, used as part of the solar reflector, covered by several strips of nickel sheet metal. When the parabolic dish collector was operational, the temperature of water was 60 oC in rectangular receiver tank, 75 0C within the copper coil and 125 oC in radiator device receiver. For rectangular receiver tank, hot water obtained within time (2 h), for copper coil receiver tank, hot water obtained within time (30 min) and for radiator heat exchanger receiver, steam obtained within time (20 min).